Philip Melanchthon : orations on philosophy and education (Cambridge texts in the history of philosophy, 1999)
The scope of education. 1. On the order of learning. 2. On the role of the schools. 3. On the distinction between the Gospel and philosophy -- The arts course. 4. On the study of languages. 5. Preface to Homer. 6. On the usefulness of fables. 7. Praise of eloquence. 8. Preface to Cicero's On Duties. 9. Dedicatory letter to the Questions on Dialectics. 10. Preface to arithmetic. 11. Preface to geometry. 12. Preface to On the Sphere. 13. On astronomy and geography. 14. The dignity of astrology. 15. On philosophy. 16. On natural philosophy. 17. Dedicatory letter to the Epitome of Moral Philosophy. 18. Preface to the Commentary on the Soul. 19. Preface to the Book on the Soul. 20. On anatomy -- The higher faculties. 21. On the merit of the art of medicine. 22. On the merit of laws. 23. On the merit of studying theology -- Authorities. 24. On Plato. 25. On Aristotle. 26. On the life of Galen. 27. On the life of Avicenna. 28. On the life of Rudolf Agricola